An Examination of the Relationships between Psychological Resilience, Organizational Ostracism, and Burnout in K-12 Teachers through Structural Equation Modelling - Polat, Hakan; Karakose, Turgut; Ozdemir, Tuncay Yavuz; Tulubas, Tijen; Yirci, Ramazan; Demirkol, Murat (Mdpi, 2023)
Psychological resilience, burnout, and ostracism are significant variables that may affect teachers' performance and well-being. While psychological resilience is the ability of individuals to cope with the challenges of life/work and could support teachers in performing their profession, burnout (i.e., high levels of emotional exhaustion and desensitization) and ostracism (i.e., being ignored by others in the workplace) could lead to serious negative outcomes for both teachers and the educational system. Despite their significance, studies addressing the relationships between these variables are rare. Therefore, this study aimed to investigate the relationships between teachers' psychological resilience, burnout, and organizational ostracism. The study used structural equation modeling (SEM) to test the hypothetical relationships between these variables. The participants were selected using a simple random sampling method among K-12 teachers working in Elazig, Turkey. The data were collected using Psychological Resilience Scale-Short Form, Organizational Ostracism Scale, and Burnout Syndrome Inventory-Short Form. Data obtained from 309 K-12 teachers were analyzed using path analysis. The findings showed that teachers' psychological resilience was quite low, whilst they experienced high levels of burnout and organizational ostracism. The results also showed a negative relationship between their psychological resilience and organizational ostracism and burnout while determining a positive relationship between ostracism and burnout. Psychological resilience was determined to have a moderating role in the relationship between organizational ostracism and burnout. Implications were suggested for both research and practice.
Keywords: psychological resilience; organizational ostracism; burnout; K-12 teachers; exclusion; structural equation modelling